Proceedings Frontiers in Education 35th Annual Conference
DOI: 10.1109/fie.2005.1612246
|View full text |Cite
|
Sign up to set email alerts
|

Computer Anxiety, Self-Efficacy, Computer Experience: An investigation throughout a Computer Science degree

Abstract: Considerable research has focused on the relationship between computer experience, computer anxiety and self-efficacy. These factors have been used both individually and in combination as predictors in the social sciences and business studies [1, 7, 17]. However, very few studies investigate their effects in the area of computer science. This study focuses on capturing these factors across the four years of a computer science course at Trinity College, Dublin. It shows that as computer experience increases sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Studies have revealed that teachers cannot use technology in the education process to increase learning and that they do not feel ready (Haydn and Barton, 2007). However, computer is one of the developing technologies and it is important to use computers both in daily life and in educational environments as a teaching aid (Durkin et al, 2010). This enables many people to gain experience directly or indirectly about computer usage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that teachers cannot use technology in the education process to increase learning and that they do not feel ready (Haydn and Barton, 2007). However, computer is one of the developing technologies and it is important to use computers both in daily life and in educational environments as a teaching aid (Durkin et al, 2010). This enables many people to gain experience directly or indirectly about computer usage.…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, computer self-efficacy is defined as an important structure that affects one's belief in his/her computer usage skills; and teachers' usage of computers in classroom (Albion, 1999). Studies of literature on computer self-efficacy determine that people whose computer selfefficacy belief is high are more eager when using computers, their anxieties about the computer is lower, they keep pace with the technological developments more quickly, they trust themselves in challenges about computers, and they are more successful in resolving these issues (Doyle et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Ref. [27] found that as computer experience increases, self-efficacy also increases while computer anxiety decreases. We expect that experience with the computer not only decreases computer anxiety but also anxiety related to other technological tools, and specifically influence positively teachers' perceptions of the interactive board.…”
Section: B Research Hypothesesmentioning
confidence: 99%
“…Self-efficacy has a positive relationship with computer experience [21]. Self-efficacy and prior computer experience significantly predict and contribute to the creativity of the subjects [17].…”
Section: Self-efficacymentioning
confidence: 99%